2010
DOI: 10.1080/15389588.2010.485284
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Occupant Anthropometry and Seat Position on Ejection Risk in a Rollover

Abstract: These data suggest that assessment of ejection prevention systems using either a 50th or 5th percentile adult anthropomorphic test dummy (ATD) might provide a reasonable measure of system function for a broad range of occupants. They also support the development of ejection mitigation technologies that extend beyond the first row to protect occupants in rear seat positions. Future studies should consider potential interaction effects (i.e., occupant size and vehicle dimensions) and the influence of occupant si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…In our study, the majority of the victims were drivers (54%) and front seat (15.6%) passengers. This is similar to Atkinson et al [20] who reported a significantly higher rate of ejection among drivers in comparison to other passengers. Among unrestrained occupants, 62% of drivers and 51% of front seat passengers experienced ejection.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the majority of the victims were drivers (54%) and front seat (15.6%) passengers. This is similar to Atkinson et al [20] who reported a significantly higher rate of ejection among drivers in comparison to other passengers. Among unrestrained occupants, 62% of drivers and 51% of front seat passengers experienced ejection.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, ejection was reduced in patients in the post-implementation versus pre-implementation periods. This is similar to other studies that showed a 38% reduction rate in patines who were restrained, and another study that reported 62% of unrestrained drivers ejected from the vehicle [18][19].…”
Section: Discussionsupporting
confidence: 90%
“…Actually, these practices cannot protect a baby during a car crash. During rollover crashes, ejection increases an occupant’s risk of severe to fatal injury as compared to risks for those retained in the vehicle [ 14 ]. Thus, parents should be taught about the serious threat to their children’s lives if these children are not correctly secured in safety seats.…”
Section: Discussionmentioning
confidence: 99%